2016
DOI: 10.7224/1537-2073.2016-004
|View full text |Cite
|
Sign up to set email alerts
|

Screening Tools for Anxiety in People with Multiple Sclerosis

Abstract: Background: Anxiety is prevalent in people with multiple sclerosis (MS). Screening measures are used to identify symptoms of anxiety, but the optimal measure to screen for anxiety disorders in MS has not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
0
24
0
3
Order By: Relevance
“…A recent systematic review of the validity and reliability of anxiety measures found that only the HADS, GAD-7 and BAI had been assessed in MS (Litster et al, 2016); criterion validity of the GAD-7 had not been assessed, and reliability had not been assessed for the HADS or GAD-7. At the proposed cut-points for the general population the sensitivity of the GAD-7 was unacceptably low in our MS population, given that it was designed as a screen specifically for generalized anxiety disorder, while sensitivities for the other measures were modestly better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of the validity and reliability of anxiety measures found that only the HADS, GAD-7 and BAI had been assessed in MS (Litster et al, 2016); criterion validity of the GAD-7 had not been assessed, and reliability had not been assessed for the HADS or GAD-7. At the proposed cut-points for the general population the sensitivity of the GAD-7 was unacceptably low in our MS population, given that it was designed as a screen specifically for generalized anxiety disorder, while sensitivities for the other measures were modestly better.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review identified 21 studies which assessed the performance of nine depression screening measures in MS and found that further research was needed to assess the utility of most measures (Hind et al, 2016). A systematic review of screening measures for anxiety found relatively little support for the validity and reliability of three available instruments, the Hospital Anxiety and Depression Scale (HADS), Generalized Anxiety Disorder-7 (GAD-7) and BAI (Litster et al, 2016). Therefore, we aimed to evaluate the validity and reliability of multiple screening measures for depression and anxiety for people with MS.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst several papers have reported good reliability and validity (Maier et al, 1988;Clark and Donvan, 1994;Mondolo et al, 2006;Kummer et al, 2010;Leentjens et al, 2011) with acceptable Cronbach alpha scores were reported in numerous studies (Bjelland et al, 2002;García-Campayo et al, 2012;Chouhan et al, 2016;Erge et al, 2016). However, both Scott et al (2017) and Litster et al (2016) reported little support for the validity and reliability of the HAM-A. The factors structure of the instrument is not standardised, influenced by the medical condition being investigated, ranging from one to a four structure as fitting the data equally well (Bjelland et al, 2002;Leentjens et al, 2011;Cosco et al, 2012;Hung et al, 2015;Scott et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, screening tools must be validated in the IMID populations. To date, these validation efforts have been limited to a few tools, and evaluation of psychometric characteristics of these tools has been limited [ 28 - 30 ].…”
Section: Introductionmentioning
confidence: 99%